The Role of School Principals in Employing Digital Learning from the Point of View of Teachers in Basic Education Schools in North Al Batinah Governorate, Sultanate of Oman (The International Journal for Scientific Research, 2024)
This study sought to identify the role of school administrators in employing digital learning from the point of view of teachers in basic education schools in the governorate of North Al Batinah in the Sultanate of Oman , and the researchers  followed the descriptive analytical curriculum because it is the most suitable for such studies, and the study community consists of teachers of schools in the governorate of North Al Batinah, and a random sample of (502) teachers from the study community was selected, and the researchers  used the questionnaire as a tool for her study, and this study has reached several results, the most important of which are: The researchers  recommends working on developing the skills of school principals, their abilities to use digital technology, activating the community partnership between the school and the community to increase the culture of digital learning among community members, the need to train teachers and students on the use of digital tools, and conducting more field research related to the activation of digital learning.
Keywords: Role; School Principal; Basic Education; Digital Learning